Penguatan Kompetensi Pedagogik Mahasiswa Melalui PKM Internasional di Eakkapapsasanawich Islamic Shool, Krabi, Thailand - Salamah, Siti Zahro; Putra, Aidil Syah; Haerudin, Haerudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
This international Community Service Program aimed to strengthen students’ pedagogical competence through English teaching practice in a multicultural Islamic school. The program was conducted at Eakkapapsasanawich Islamic School (EKP), Krabi, Thailand, from November 10, 2025, to January 5, 2026. A qualitative descriptive approach was applied through 50 speaking-intensive teaching sessions involving 77 secondary students. Teaching strategies included Universal Design for Learning (UDL), Indonesian song-based ice-breakers, educational games, and simple digital media. Data were collected through observation, activity logbooks, lesson plans, and reflections. The results showed a 42% improvement in students’ speaking ability, the production of two teaching modules, and the implementation of 85 supporting academic and non-academic activities. This program contributed to enhancing pedagogical competence and cultural awareness among pre-service teachers.